BIODIESEL FROM NYAMPLUNG (CALOPHYLLUM INOPHYLLUM) SEED OIL WITH A TRANSESTERIFICATION PROCESS USING A CONTINOUS FLOW SYSTEM IN THE REACTOR - Pramana, yanatra budi; Yakin, Ainul; Putri, Nani Sari; Huda, Achmad Miftahul (UNIPA PRESS, 2019)
Biodiesel production from calophyllum inophyllum be obtained via esterification and transesterification, using two continuous reactors with catalyst NaOH at a concentration (0.4 ;0.6,0.8; 1) wt%, calophyllum inophyllum seed oil and reaction temperature (40, 50,60)oC. This research was to determine the effect of catalyst amount and reaction temperature on transesterification of calophyllum inophyllum seed toward yield Fatty Acid Methyl Ester . The last step is analysis yield of Fatty Acid Methyl Ester with Gas Chromatography (GC). The highest yield is obtained on the amount of 1% NaOH catalyst and at a temperature of 60oC with yield of 87.036%.